PRODUCTION OF CALLUS BIOMASS AND ANTIOXIDANT SECONDARY METABOLITES IN BLACK CUMIN - A. Bibi; M. A. Khan; M. Adil; Z. U. R. Mashwani (Journal of Animal and Plant Sciences, 2018)
Black cumin (Nigella sativa) is a medicinally significant plant species, used traditionally against a variety of diseases. In this investigation, efficient methods for in vitro seed germination and callus formation were developed. Further, the antioxidant potential was determined in the regenerated tissues. The results showed highest germination frequency in the black cumin seeds when incubated on MS (Murashige and Skoog, 1962) medium supplemented with 1.0 mg/L Gibberellic acid ( GA ). Among the different pretreatment solutions, H O favored highest germination frequency 3 2 2 followed by KNO . Callus biomass formation was initiated in cotyledon explants, and highest callus induction frequency 3 (88%) was observed on MS media supplemented with 4.0 mg/L Thidiazuron (T DZ) plus 4.0 mg/L ±-naphthalene acetic acid (NAA) . In callus cultures, growth kinetics was inspected to determine the impact of culture period on antioxidant potential in relation to biomass accumulation. Highest dry biomass ( 13.2 mg/l) was recorded on day 35 of the growth curve at TDZ+NAA (4.0 mg/L; each). Further, more phenolics ( TPC: 1.48 mg) and flavanoids (TFC: 0.58) were detected in calli harvested on day 35. Moreover, the DPPH radical scavenging activity in the callus cultures of black cumin was observed in correlation with accumulation of dry biomass. Abbreviations: PGR=Plant growth regulator, DBM=Dry bio mass, TPC= Total phenolic content, TFC= Total flavonoid content, FRSA=Free radical scavenging activity, MS= Murashige and Skoog, DPPH= 1,1-diphenyl-2-picryl-hydrazyl et al. 2013) . In vitro seed germination is a good strategy
Keywords: Black cumin; callus; growth curve; phenolics; antioxidant activity.